The education of radical democracy - Amsler, Sarah (Routledge, 2015)
The Education of Radical Democracy explores why radical democracy is so necessary, difficult, and possible and why it is important to understand it as an educative activity . The book draws on critical social theory and critical pedagogy to explain what enables and sustains work for radical democratization, and considers how we can begin such work in neoliberal societies today. Exploring examples of projects from the nineteenth century to the present day, the book sheds light on a wealth of critical tools, research studies, theoretical concepts and practical methods. It offers a critical reading of the ‘crisis of hope’ in neoliberal capitalist societies, focusing on the problem of the ‘contraction of possibilities’ for democratic agency, resistance to domination, and practices of freedom. It argues that radically democratic thinking, practice, and forms of social organization are vital for countering and overcoming systemic hegemonies and that these can be learned and cultivated.